2013
DOI: 10.1007/s10803-013-1898-4
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Smiles of a Child with Autism Spectrum Disorder During an Animal-assisted Activity May Facilitate Social Positive Behaviors—Quantitative Analysis with Smile-detecting Interface

Abstract: We quantitatively measured the smiles of a child with autism spectrum disorder (ASD-C) using a wearable interface device during animal-assisted activities (AAA) for 7 months, and compared the results with a control of the same age. The participant was a 10-year-old boy with ASD, and a normal healthy boy of the same age was the control. They voluntarily participated in this study. Neither child had difficulty putting on the wearable device. They kept putting on the device comfortably through the entire experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 16 publications
1
55
0
9
Order By: Relevance
“…Several studies using horses [9] [10] or dogs [11] have been conducted, reporting that positive social behaviors (e.g., smiling and positive physical contact) increased. We also have examined AAA with dogs and verified that participants' positive social behaviors and facial expressions (e.g., smiles) increased by using a wearable device measuring facial expressions during the activity [12]. However, previous AAA studies have evaluation difficulties because animal behaviors cannot be controlled because a quantitative description of animals' behavior is difficult.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Several studies using horses [9] [10] or dogs [11] have been conducted, reporting that positive social behaviors (e.g., smiling and positive physical contact) increased. We also have examined AAA with dogs and verified that participants' positive social behaviors and facial expressions (e.g., smiles) increased by using a wearable device measuring facial expressions during the activity [12]. However, previous AAA studies have evaluation difficulties because animal behaviors cannot be controlled because a quantitative description of animals' behavior is difficult.…”
Section: Introductionmentioning
confidence: 79%
“…We proposed a comprehensive framework called ARAA for children with ASD to facilitate their social interaction and communication skills based on the concept of AAA with psychoeducational approach [12]. The main approach was to encourage children to produce self-initiated positive social behaviors based on their positive emotional responses through a child-driven, improvised interaction via quantitative evidence-based evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A case study which involved 14 sessions of animal-assisted play therapy demonstrated that it helped improve social communication, including joint attention and waiting behaviors [30]. Likewise, the smile caused during animal-assisted activities has been reported to improve positive social behaviors and decreased negative social behaviors [31]. It has also been reported that the presence of a pig in the classroom, with contact time with the animal was at least 40 min/week, helped improve social functioning, social approach behaviors decreased social withdrawal behaviors and increased social skills [32].…”
Section: Mind-body Interventionsmentioning
confidence: 99%